2020
DOI: 10.1021/acs.jpcc.0c08444
|View full text |Cite
|
Sign up to set email alerts
|

Enabling High Dielectric Response in PVDF/V2C MXene–TiO2 Composites Based on Nontypical V–F–Ti Bonding and Fermi-Level Overlapping Mechanisms

Abstract: High dielectric constant and breakdown strength are crucial for high-energy-density polymer/ceramic composites. Anatase-TiO2 with low dielectric constant and V2C MXene with high work function are not satisfactory fillers. In the present work, V2C–TiO2 hybrid filler was in situ synthesized, followed by fabricating poly­(vinylidene fluoride) (PVDF)/V2C–TiO2 composites via solution cast. Compared with PVDF/TiO2 and PVDF/V2C composites, PVDF/V2C–TiO2 composites have an improved high dielectric constant, depressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…[13] It was observed that for the V 2 C sample, a strong peak that appears at 2θ $ 7.5 corresponds to the 002 plane. [17,28] When V 2 AlC was exposed to the LiF/HCl mixture during synthesis, the 002 peak of V 2 AlC shifted to lower 2θ angles. The shift of the 002 peak from 13.5 to 7.5 corresponds to a dspacing increase from $6.58 to $11.8 Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] It was observed that for the V 2 C sample, a strong peak that appears at 2θ $ 7.5 corresponds to the 002 plane. [17,28] When V 2 AlC was exposed to the LiF/HCl mixture during synthesis, the 002 peak of V 2 AlC shifted to lower 2θ angles. The shift of the 002 peak from 13.5 to 7.5 corresponds to a dspacing increase from $6.58 to $11.8 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The PVDF/V 2 C‐TiO 2 composite has been used to show an improved dielectric constant. [ 17 ] In this regard, cellulose nanofibers (CNFs) are considered as an ideal material for the development of environmentally friendly composites. [ 18 ] Properties like renewability, sustainability, and biocompatibility make CNF a potential candidate for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, carbon nanotubes (CNTs), 14,15 graphene, 15,16 or carbon black 17,18 are used for mechanical reinforcement and for increasing the electrical conductivity; ionic liquids 19,20 are used to improve the ionic conductivity or induce a thermochromic response, for example; magnetic nano-and microparticles 21,22 are used to induce a magnetic response to the polymer matrix; and metal−organic frameworks 23,24 mechanical or dielectric properties and absorption capabilities, among others. Many advances have been achieved in the enhancement of the dielectric response, 25 electrochemical properties, 26 and electrical conductivity 27 in PVDF-based composites. However, these studies mainly focus on improving or inducing a single functionality in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Many advances have been achieved in the enhancement of the dielectric response, electrochemical properties, and electrical conductivity in PVDF-based composites. However, these studies mainly focus on improving or inducing a single functionality in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous development of electric vehicles, defense industry, and smart grids have caused high energy storage devices to attract more and more attention. Among various energy storage methods, polymer film capacitors have become the ideal type due to their inherent mechanical properties, ease of processing, low cost advantages, and excellent dielectric properties. , Since the polymer film stores and releases energy by static polarization and depolarization, it has the advantages of high charge–discharge efficiency and environmental protection. However, the dielectric constant of dielectric materials used in commercial film capacitors is usually low, such as 2.25 for biaxially oriented polypropylene (BOPP), which results in a low discharge energy density of only 3 J/cm 3 . Therefore, the preparation of thin film materials with high permittivity and breakdown strength has been a hotspot and nodus recently.…”
Section: Introductionmentioning
confidence: 99%